E-business Development: The Comparative Study of the Czech Republic and the Ukraine - Victoriya Kulyk; Dagmar Škodová Parmová (DETUROPE)
This paper summarizes the current basis for e-business development in the EU with the focus on the Czech Republic with comparison with the associated Ukraine. After description of managerial and accountancy aspects for the e-commerce way of selling goods and services and after summarizing the legislative framework there is an analyses for future Human Resources Management according to the needs of Industry 4.0 introduced. After this theoretical part there you can find the comparison of the particular tools for e-business support and training of employees in related services between the Czech Republic and the Ukraine. As conclusion there is a list of recommendation summarized with the focus on how to improve the situation of e-business in nowadays Ukraine.